Virtual Oscillator Control Strategy for Parallel Operated Inverter in an Isolated Microgrid - Puskar Neupane; Dixant Bikal Sapkota; Bivek Shiwakoti; Saugat Baral (KEC Journal of Science and Engineering, 2025)
This study focuses on the application of Virtual Oscillator Control (VOC) to enhance the stability and performance of isolated microgrids in renewable energy systems. VOC operates by generating periodic signals internally using principles of nonlinear oscillation, such as the Lienard theorem and the Van der Pol oscillator. This approach eliminates the need for real-time grid measurements, enabling faster response times. The research investigates VOC's implementation in both single-phase and three-phase microgrids, analyzing its impact on system stability and performance. Simulation models include microgrids with multiple VOC inverters for power-sharing and systems combining VOC with PV inverters to evaluate compatibility. The results highlight VOC’s ability to improve stability, enable effective power-sharing, enhance transient recovery, and reduce response times, demonstrating its potential as a robust solution for grid-forming inverters in renewable energy integration.